The world's scariest zombies - Hamilton, S.L. (Abdo Publishing, a division of ABDO, 2021)
This title introduces you to one of the world's most popular legendary monsters. Your readers will learn about the real-life history surrounding zombies and see how the creatures are reflected in different cultures. Features include a table of contents, glossary, and index. Plus, an Xtreme Challenge page with content questions help readers process and build upon their zombie knowledge.